Economic theory and international trade : essays in honour of Murray C. Kemp - Woodland, A. D.; Kemp, Murray C. (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2002)
Important issues in economic theory and international trade are addressed in this volume with contributions from internationally renowned researchers. Topics covered include classical trade theory and welfare economics, international trade policy, economic dynamics and international economics.
Includes bibliographical references and index.
aia 12/8/16
Loans
Keywords: International trade; Commercial policy; Economics